Morfološke pogreške u diskursu djece s PJT - Arapović, Diana; Anđel, Maja (2003)
The notion of Specific Language Impairment (SLI) refers to children whose language skills are in disproportion with their chronological age and their non-verbal skills, for unknown reasons and in any (one or more) part of their linguistic development (Bishop, Adams 1991). SLI children may have difficulties in the phonological and pragmatic language aspects, but the morphosyntactic aspect seems to be the most affected part of grammar in SLI children. Morphology is the part of the language in which the grammaticalness of a language system becomes clearly perceptible, therefore it is especially important when we try to assess the level of language skills. In written paper we have tried to present the level of morphology acquisition in children with SLI, taking into consideration the morphological complexity of Croatian language. We have examined morphological errors in 51 children with SLI, age from 4, 2 to 8 years. Our results show that most errors appear in categories of inflexion and congruency, i.e. inappropriate case ending for nouns, auxiliary omissions for verbs and morphological incompatibility of noun+adjective combinations. These results suggest that children with SLI are not able to communicate the contents of an information and take care of its correct grammatical form at the same time.
Projekt MZOS
Projekt MZOS
HRV